FAKTOR PENGHAMBAT MAHASISWA MENYELESAIKAN SKRIPSI PRODI PENDIDIKAN SENI RUPA FBS UNP - FINDA GENINOVA LISA, Drs. Wisdiarman, M. Pd, Drs. Suib Awrus, M. Pd (Serupa The Journal of Art Education, 2013)
The purpose of this study were to determine : internal and external factors that become obstacles in completing the thesis student of visual arts Education Program FBS UNP. Type of research is a quantitative study using descriptive with 37 people as the sample. Data sources of this study are 2007 and 2008 students of visual arts education program FBS UNP who enrolled in thesis course in january-june 2013. Research findings of internal and external factors with seven indicators and enviromental factors as the highest factor in 56.8% percentage, motivation 54.1%, intelligence and parental factor in 51.4%, interest and discipline in 48.6% and the last is creativity in 40.5%. those all are in the high category. Key words : Obstacles in completing, Thesis